Evaluation of agar-gel immuno diffusion and counter current immuno electrophoresis in the diagnosis of hydatidosis in cattle and buffaloes - Konapur, S G; Panduranga, G L; Sastry, K N V; Jagannath, M S; Rajasekhar, M (The Indian Journal of Animal Sciences, 2012)
The sensitivity and specificity of AGID test using concentrated crude and partially purified antigens were found to be 80 and 83.9% in cattle and 50 and 84.84% in buffaloes respectively. The sensitivity and specificity of CCIEP test using concentrated crude and partially purified antigens were 90.7 and 88.1 % in cattle and 69.2 and 87.8% in buffaloes respectively. In routine, field screening of animals for hydatidosis by AGID with concentrated crude antigens of fluid and protoscoleces intense precipitation reactions were observed.